2015
DOI: 10.1094/cchem-03-15-0045-r
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Submicron‐Scale Rice Flour Produced by Wet Media Grinding

Abstract: Cereal Chem. 93(1):53-57The digestibility and hydration properties of wet-ground submicron-scale rice flour were compared with those of dry-ground coarser microscale flours. The submicron flour (mean size 0.6 µm) was produced in a wet-media mill with 0.3 mm zirconia beads by continuous 24 h pulverization. The solubility, water absorption index, and swelling power increased as the mean particle size decreased, reaching maximum values in the submicron flour.Starch damage was high in the submicron flour, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Thus, the accessibility and surface/volume ratio of particles significantly affect the SMD. The fragmentation of particles leads to the enlargement of the particle surface, which in turn promotes the digestion by enzymes [5,29,30]. This negative correlation between the particle size distribution and the starch modification degree (SMD) was also confirmed in the present study: while an exclusively thermal treatment of starch and flour did not result in an enhanced starch modification degree (SMD) and or the shift of PSD to smaller sizes (Figure 4A), mechanical treatments with/without thermal forces (MS and TMS) led to a decrease in particle size of wheat flours and an increase in SMD (compare Figure 4B), which is in agreement with other studies, analyzing the effects of grinding on starch modification and particle size [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the accessibility and surface/volume ratio of particles significantly affect the SMD. The fragmentation of particles leads to the enlargement of the particle surface, which in turn promotes the digestion by enzymes [5,29,30]. This negative correlation between the particle size distribution and the starch modification degree (SMD) was also confirmed in the present study: while an exclusively thermal treatment of starch and flour did not result in an enhanced starch modification degree (SMD) and or the shift of PSD to smaller sizes (Figure 4A), mechanical treatments with/without thermal forces (MS and TMS) led to a decrease in particle size of wheat flours and an increase in SMD (compare Figure 4B), which is in agreement with other studies, analyzing the effects of grinding on starch modification and particle size [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…The lower degree of hydrolysis can effectively reduce the rise in blood glucose after meals [16]. Hosson et al (2015) compared the digestibility of hammer-milled flour, jet-milled flour, and submicron-scale WRF and suggested that submicron-scale WRF was more easily digested [17]. Lee et al (2019) compared hammer milling and air jet milling, using germinated brown rice as the sample.…”
Section: Introductionmentioning
confidence: 99%